PENGEMBANGAN MEDIA POWER POINT INTERAKTIF PADA PEMBELAJARAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Chandra, Milke Audina; Poerwanti, Endang; Mukhlishina, Innany (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
Media is a tool that teachers use to convey material during the learning process. Therefore, media is very important to use during the learning process. The aim of this research is to produce digital-based media, namely interactive power points, which are suitable for use to help students who have difficulty reading and can attract interest in reading in grade 1 elementary school students. The type of research used is development research or Research and Development (R&D). The method used is experimental. The research model used is the Addie model from Dick and Carey. The data collection techniques used were observation and interviews. The results of material expert validation and media expert validation stated that interactive PowerPoint media was very suitable for use and did not need revision. The value obtained from material expert validation was 84% and from media expert validation the value was 80%. Power point media was declared very suitable by getting the category very well used and implemented for reading learning at the beginning of grade 1 of elementary school. The students' response was very good, it can be seen that students felt enthusiastic when learning using interactive power point media. Therefore, this power point media can be used for initial reading learning and increasing reading interest in grade 1 elementary school students.